Gonadal Cycle-Dependent Expression of Genes Encoding Peptide-, Growth Factor-, and Orphan G-Protein-Coupled Receptors in Gonadotropin- Releasing Hormone Neurons of Mice - Vastagh, Csaba; Csillag, Veronika; Solymosi, Norbert; Farkas, Imre; Liposits, Zsolt (Frontiers in Molecular Neuroscience, 2021)
Rising serum estradiol triggers the surge release of gonadotropin-releasing hormone (GnRH) at late proestrus leading to ovulation. We hypothesized that proestrus evokes alterations in peptidergic signaling onto GnRH neurons inducing a differential expression of neuropeptide-, growth factor-, and orphan G-protein-coupled receptor (GPCR) genes. Thus, we analyzed the transcriptome of GnRH neurons collected from intact, proestrous and metestrous GnRH-green fluorescent protein (GnRH-GFP) transgenic mice using Affymetrix microarray technique. Proestrus resulted in a differential expression of genes coding for peptide/neuropeptide receptors including Adipor1, Prokr1, Ednrb, Rtn4r, Nmbr, Acvr2b, Sctr, Npr3, Nmur1, Mc3r, Cckbr, and Amhr2. In this gene cluster, Adipor1 mRNA expression was upregulated and the others were downregulated. Expression of growth factor receptors and their related proteins was also altered showing upregulation of Fgfr1, Igf1r, Grb2, Grb10, and Ngfrap1 and downregulation of Egfr and Tgfbr2 genes. Gpr107, an orphan GPCR, was upregulated during proestrus, while others were significantly downregulated (Gpr1, Gpr87, Gpr18, Gpr62, Gpr125, Gpr183, Gpr4, and Gpr88). Further affected receptors included vomeronasal receptors (Vmn1r172, Vmn2r-ps54, and Vmn1r148) and platelet-activating factor receptor (Ptafr), all with marked downregulation. Patch-clamp recordings from mouse GnRH-GFP neurons carried out at metestrus confirmed that the differentially expressed IGF-1, secretin, and GPR107 receptors were operational, as their activation by specific ligands evoked an increase in the frequency of miniature postsynaptic currents (mPSCs). These findings show the contribution of certain novel peptides, growth factors, and ligands of orphan GPCRs to regulation of GnRH neurons and their preparation for the surge release.